Safety and efficacy of simultaneous colorectal ESD for large synchronous colorectal lesions - Chiba, Hideyuki; Tachikawa, Jun; Kurihara, Daisuke; Ashikari, Keiichi; Goto, Toru; Takahashi, Akihiro; Sakai, Eiji; Ohata, Ken; Nakajima, Atsushi (Endoscopy International Open, 2017)
Background and study aims Multiple large colorectal lesions are sometimes diagnosed during colonoscopy. However, there have been no investigations of the feasibility of simultaneous endoscopic submucosal dissection (ESD) for multiple lesions. This study aims to reveal the strategy of simultaneous ESD for multiple large colorectal lesions.Patients and methods 246 patients who underwent ESD for 274 colorectal lesions were retrospectively evaluated in this study. Fifty-one large colorectal lesions among 23 patients were treated by ESD simultaneously (simultaneous group), and 223 patients were treated with ESD for a single lesion (single group).Results En-bloc resection and curative resection rates did not differ. Compared with the single group, each procedure time was faster (31.8 ± 23.6 min vs. 45.8 ± 44.8, P = 0.002), but total procedure time was significantly longer in the simultaneous group (70.6 ± 33.4 vs. 45.8 ± 44.8 min, P = 0.01). Rates of adverse events including bleeding and perforation were not higher in the simultaneous group but the mean blood pressure, incidence of bradycardia and the amount of sedative drug used during ESD were significantly higher in the simultaneous group. Multiple logistic regression analysis identified non-experienced physician, lesion size ≥ 40 mm and submucosal fibrosis as an independent risk factor for procedure duration (≥ 90 min) (Odds ratio 11.852, 18.280, and 3.672; P < 0.05, respectively).Conclusions Simultaneous ESD for multiple synchronous colorectal lesions is safe and feasible compared with single ESD and can reduce the burden to patients, length of hospital stay and medical expense. These results need to be elucidated by further studies.